PENERAPAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS AUGMENTED REALITY DALAM MENINGKATKAN MOTIVASI BELAJAR DI SMP ISLAM AL-WASI MAROS - Nurlaela; Bunyamin, Andi; Syahrul, Muhammad; Surani; Subaedah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the implementation of Augmented Reality (AR)-based interactive learning media to enhance student learning motivation in the Islamic Religious Education subject for Grade VIII students at SMP Islam Al-Wasi Maros. The study employed the Classroom Action Research (CAR) method, conducted over two cycles, with each cycle comprising the stages of planning, implementation, observation, and reflection. The research subjects consisted of 32 Grade VIII students. Data collection techniques included observation, learning motivation questionnaires, documentation, and learning evaluations. The results indicate that prior to the implementation of AR media, student learning motivation fell into the